2016
DOI: 10.1111/echo.13163
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart Involvement in Patients with Sarcoidosis

Abstract: The left ventricle (LV) is affected in 20-25% of patients with sarcoidosis and its involvement is associated with morbidity and mortality. However, effects of sarcoidosis on the right ventricle (RV) are not well documented. Our aims were to investigate the prevalence of RV dysfunction in patients with sarcoidosis and determine whether it is predominantly associated with direct cardiac involvement, severity of lung disease, or pulmonary hypertension (PH). We identified 50 patients with biopsy-proven extra-cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 16 publications
1
20
0
2
Order By: Relevance
“…17 According to Patel et al study, 56% of patients had right ventricular dysfunction, and these changes could be associated with the absence of left ventricular dysfunction or even independent of pulmonary function impairment. 18 Schouver et al showed that the total left ventricular strain or LV GLS in the sarcoidosis patients was reduced compared to the control group, 19 which was consistent with our results. In their study, the LV GLS index was an important indicator in the evaluation of cardiac sarcoidosis.…”
Section: Discussionsupporting
confidence: 92%
“…17 According to Patel et al study, 56% of patients had right ventricular dysfunction, and these changes could be associated with the absence of left ventricular dysfunction or even independent of pulmonary function impairment. 18 Schouver et al showed that the total left ventricular strain or LV GLS in the sarcoidosis patients was reduced compared to the control group, 19 which was consistent with our results. In their study, the LV GLS index was an important indicator in the evaluation of cardiac sarcoidosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our systematic review identified 137 potentially relevant articles; the full text of 13 was reviewed and 9 were selected. None of the studies compared TTE to no testing; rather, all were nonrandomized studies that selected patients with sarcoidosis (most enrolled patients who had persistent respiratory symptoms despite treatment of their sarcoidosis) and reported the frequency of abnormal TTE results (180,184,(191)(192)(193)(194)(195)(196)(197). Some studies also reported the rate of confirmation by right heart catheterization.…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…23 Further, a reduced global longitudinal strain is an independent predictor of adverse events among patients with suspected cardiac sarcoidosis. 25 The presence of LGE on CMR, including focal LGE, 76 and the extent of LGE (LGE mass C20% of LV mass), is associated with a higher risk of death or VT and a lower likelihood of improvement in LV function. 83,99 The prognostic value of other CMR findings have been less well studied and no reports are available for T2 weighted CMR.…”
Section: Prognosismentioning
confidence: 99%